a) \(4x\left(5x+2\right)-\left(10x-3\right)\left(2x+7\right)=133\)
\(=\left(20x^2+8x\right)-\left(20x^2+64x-21\right)=133\)
\(=20x^2+8x-20x^2-64x+21=133\)
\(=-56x=112\)
\(\Leftrightarrow x=-2\)
b) \(4\left(x-1\right)\left(x+5\right)+\left(x+2\right)\left(x+5\right)=5\left(x-1\right)\left(x+2\right)\)
\(\Leftrightarrow\left(x+5\right)\left(4x-4+x+2\right)=5\left(x-1\right)\left(x+2\right)\)
\(\Leftrightarrow\left(x+5\right)\left(5x-2\right)=\left(5x-5\right)\left(x+2\right)\)
\(\Leftrightarrow5x^2+23x-10=5x^2+5x-10\)
\(\Leftrightarrow23x=5x\)
\(\Leftrightarrow18x=0\Leftrightarrow x=0\)
a) \(4x\left(5x+2\right)-\left(10x-3\right)\left(2x+7\right)=133\)
\(\Leftrightarrow20x^2+8x-\left[10x.\left(2x+7\right)-3.\left(2x+7\right)\right]=133\)
\(\Leftrightarrow20x^2+8x-\left(20x^2+70x-6x-21\right)=133\)
\(\Leftrightarrow20x^2+8x-20x^2-70x+6x+21=133\)
\(\Leftrightarrow8x-70x+6x=133-21\)
\(\Leftrightarrow-56x=112\)
\(\Leftrightarrow x=-\frac{112}{56}=-2\)
Vậy : \(x=-2\)